(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article are presented some discrete parts of politicization Islam. Region acted main role in the human history of developing of culture, country, and moral. Modern processes of globalization and unilaterally understood modernization infl uence on traditional functions of region, especially Islam. Politicization of Islam – is one aftermath of this processes. In the article analyzed tops of politicization region negative infl uences on the sociocultural integrity and stability of modern society, else on Kazakh society. Key words: islam, ethnic identity, tolerance, religious identity, globalization.